Intraoperative small bowel length measurements and analysis of demographic predictors of increased length. Issue 7 (20th March 2013) - Teitelbaum, Ezra N.; Vaziri, Khashayar; Zettervall, Sara; Amdur, Richard L.; Orkin, Bruce A.
<x xml:space="preserve">Abstract</x> Few studies have measured small bowel length (SBL) in live humans and many textbooks base their "normal" SBL values on cadaver data. Here, we present a series of intraoperative SBL measurements and analyze predictors of increased length. SBL from ligament of Treitz to ileocecal valve was measured in patients undergoing laparotomy for colorectal resection. Patients with Crohn's disease and those who had undergone prior bowel resections were excluded. In the 240 patients studied, mean SBL was 506 ± 105 (285–845) cm. Height was positively associated with increased SBL (P < 0.001) and men had longer SBL than women (533 vs. 482 cm, P < 0.001). A multivariate linear regression model using patient sex, age, height and weight was significant (P = 0.001) and the predictors explained 8% of the variance in SBL. In this model, only height was independently predictive of increased SBL (P = 0.03). Correlation results differed between sexes. In men, height correlated with increased SBL (r = 0.20; P = 0.03), whereas in women it did not. In men, age had a positive correlation with SBL at a trend level (r = 0.17; P = 0.08), whereas in women age had a negative correlation with SBL (r = −0.18; P = 0.04). The mean SBL was 506 cm in live patients, as compared with the 600–700 cm range derived from prior cadaver studies. Male sex and height had positive correlations with SBL. SBL may decrease with age in women but not in men. Clin. Anat. 26:827–832, 2013. © 2013 Wiley Periodicals, Inc.